Signalling of multiple interleukin (IL)‐17 family cytokines via IL‐17 receptor A drives psoriasis‐related inflammatory pathways. (31st May 2021) - Tollenaere, M.A.X.; Hebsgaard, J.; Ewald, D.A.; Lovato, P.; Garcet, S.; Li, X.; Pilger, S.D.; Tiirikainen, M.L.; Bertelsen, M.; Krueger, J.G.; Norsgaard, H.
Summary: Background: The interleukin (IL)‐23/IL‐17 immune axis is of central importance in psoriasis. However, the impact of IL‐17 family cytokines other than IL‐17A in psoriasis has not been fully established. Objectives: To elucidate the contribution of IL‐17 family cytokines in psoriasis. Methods: To address the expression and localization of IL‐17 family cytokines, lesional and nonlesional skin samples from patients with psoriasis were analysed by several complementary methods, including quantitative polymerase chain reaction, immunoassays, in situ hybridization and immunohistochemistry. Mechanistic studies assessing the functional activity of IL‐17 family cytokines were performed using ex vivo cultured human skin biopsies and primary human keratinocytes. Results: We demonstrated that IL‐17A, IL‐17F, IL‐17A/F and IL‐17C are expressed at increased levels in psoriasis lesional skin and induce overlapping gene expression responses in ex vivo cultured human skin that correlate with the transcriptomic signature of psoriasis skin. Furthermore, we showed that brodalumab, in contrast to ixekizumab, normalizes gene expression responses induced by the combination of IL‐17A, IL‐17F, IL‐17A/F and IL‐17C in human keratinocytes. Conclusions: Several IL‐17 ligands signalling through IL‐17RA are overexpressed in psoriasis skin and induce similar psoriasis‐related inflammatory pathways demonstrating their relevance in relation to therapeutic intervention in psoriasis. Abstract : What is already known about this topic? The key role of interleukin (IL)‐17A in psoriasis is well established. Previous studies have shown that IL‐17A, IL‐17F and IL‐17C are overexpressed in psoriasis skin, whereas contradictory results have been published for IL‐17E. IL‐17 family cytokines induce secretion of inflammatory mediators such as antimicrobial peptides, chemokines and cytokines involved in the pathophysiology of psoriasis. What does this study add? Levels of IL‐17A/F are increased in lesional psoriasis skin but markedly lower than IL‐17A and IL‐17F. In ex vivo cultured human skin, a physiologically relevant model, IL‐17A, IL‐17F, IL‐17A/F and IL‐17C show functional redundancy in shaping the psoriasis transcriptome. IL‐17RA antagonism normalizes expression of psoriasis‐related genes in keratinocytes induced by the combination of IL‐17 family cytokines. What is the translational message? Overexpression and functional redundancy of IL‐17 family cytokines in psoriasis may explain why some patients with psoriasis with primary or secondary failure of response to secukinumab or ixekizumab achieve a clinical response after switching to brodalumab. Linked Comment: M. Sugaya. Br J Dermatol 2021; 185:483 .